Research progress of ammonia combustion toward low carbon energy - Li, Tianxin; Duan, Yuanqiang; Wang, Yueming; Zhou, Minmin; Duan, Lunbo (Fuel processing technology, 2023)
Carbon-free energy carriers like hydrogen and ammonia have drawn increasing interest as the world is committed to building a carbon-neutral future. Compared with the popular hydrogen as the fuel, ammonia still holds other significant advantages such as well-adopted production technology, energy storage and transportation. Therefore, it is necessary to conduct a comprehensive review study on the fundamentals of ammonia combustion characteristics. The main drawbacks of ammonia combustion are long ignition delay time, low laminar flame speed and noticeable NOx emissions. Some technologies including fuel blending, process intensification and combustion auxiliary technology, are introduced to remedy these drawbacks. Fuel blending system including ammonia‑hydrogen and ammonia-coal is regarded as the promising practical approach. Process intensification like preheating, pressurization, and oxygen enrichment approach is widely used to enhance the combustion via intensifying its heat and mass transfer. In addition, other combustion auxiliary technologies such as porous media and plasma-assisted are expected to bring new research opportunities for ammonia combustion application. Finally, the difficulties and challenges faced by these technologies are summarized aiming to realize the commercialization of ammonia combustion. •Ammonia combustion and emission characteristic are comprehensively reviewed.•The development and recent achievements of ammonia kinetic models are summarized.•Fuel blending and process intensification are critical in ammonia combustion.•Systemically summary of auxiliary enhanced ammonia combustion technology•The latest research on ammonia as a combustion device fuel is discussed.